Diving on damage—the muscle transcriptome of parasitic infested harbor porpoises (Phocoena phocoena) hints at oxidative stress but not hypoxia - Dönmez, Eda Merve; Siebert, Ursula; Fabrizius, Andrej (Frontiers in Marine Science, 2023)
The only native cetacean in German waters, the harbor porpoise (Phocoena phocoena), is impacted by numerous pathological lesions in the respiratory tract mainly caused by parasites or bacteria. Although harbor porpoises have been observed to not use their complete lung volume, it has not been studied whether this insufficiency leads to lower oxygen uptake, impaired diving ability, and, ultimately, reduced foraging success. This project aims to analyze whether harbor porpoises developed novel molecular adaptations to compensate impairments in oxygen supply, thus remaining viable and competitive despite the high parasitic load. Here, initial comparative transcriptome RNA sequencing (NextSeq 2000, Illumina) was performed on muscles of harbor porpoises with a respiratory tract considered as healthy and of harbor porpoises that suffered from more severe lesions and parasitic infestations in the respiratory tract. Our findings suggest an elevated response to oxidative stress in the muscles of parasitic infested harbor porpoises compared with that of healthy animals. Higher antioxidant and antiapoptotic gene expression in the muscles of non-healthy harbor porpoises might function as a compensatory effect to enhanced reactive oxygen species production and accumulation in the muscles. Simultaneously enhanced selective proteasomal degradation and myogenesis suggest a tightly controlled, finely tuned switch of the intrinsic muscle response to stress. Lipid metabolism pathways and rate-limiting transcripts involved in glycolysis were upregulated and may uphold muscle energy supply for tissue function and energy-consuming regenerative and biosynthetic processes. These preliminary results hint at a defined response of the muscle to oxidative stress that may be caused by lung tissue with more severe pathological lesions and may indicate a possible adaptation in cetaceans.